Tooth Regeneration: What We Have Now and What’s Next? - Lu, Everett; Fan, Frank (International Journal of Innovative Research in Medical Science, 2024)
Tooth regeneration gained great attention in the past decade. Researchers have explored various aspects, from partial tooth regeneration to whole tooth regeneration. Great progress has been achieved with stem cells and materials developments. However, there are still no reports about successful whole tooth growth in vitro. In this review, the recent progress on the major factors contributing to tooth regeneration were summarized including the cell sources, the scaffolds & materials, the growth factors, and the incubation systems. In addition, the potential issues and resolutions were discussed based on the available info in light of providing a full picture of the field and help for determining future directions.